Triangular approach, cultural and social mediation and its dialogues with art/education (Palíndromo, 2026)
Cultural and social mediation, along with art/education within exhibition spaces, can help promote access for diverse audiences to these venues, as art/education establishes deeper relationships between the public and the artworks. Elitist conceptions, fostered by historical approaches to art and its teaching in Brazil over the years, have discouraged the presence of diverse publics in artistic exhibition spaces. The present article addresses cultural and social mediation and art/education in the construction of two art exhibitions and their subsequent impact on a group of adolescents from a Non-Governmental Public Interest Organization (OSCIP). The study is justified by the need to promote dialogue among diverse publics, specifically focusing on adolescents aged 12 to 15 who attend the OSCIP as the research group. The general objective is to analyze the impacts of the exhibitions, which were developed based on art/educational actions grounded in the Triangular Approach and the perspective of cultural and social mediation, on the participating group. The methodology consists of a participant research design from the perspective of its technical procedures, utilizing a qualitative approach and an exploratory nature. The results highlight the importance of art/educational actions for promoting reflections on inclusion and access for different groups to artistic cultural spaces.
Keywords: art; exhibition spaces; cultural mediation; triangular approach